2015
DOI: 10.1128/mcb.00181-15
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Overexpressing Serum Retinol-Binding Protein Develop Progressive Retinal Degeneration through a Retinoid-Independent Mechanism

Abstract: Serum retinol-binding protein 4 (RBP4) is the sole specific transport protein for retinol in the blood, but it is also an adipokine with retinol-independent, proinflammatory activity associated with obesity, insulin resistance, type 2 diabetes, and cardiovascular disease. Moreover, two separate studies reported that patients with proliferative diabetic retinopathy have increased serum RBP4 levels compared to patients with mild or no retinopathy, yet the effect of increased levels of RBP4 on the retina has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 101 publications
4
46
0
Order By: Relevance
“…With the reports from Yang et al (8) and Graham et al (9) a decade ago, there has been considerable research interest focused on understanding how RBP4 synthesized by adipocytes contributes to the development of metabolic disease, including liver disease. Although much of this literature reports associations between elevated serum/plasma and/or tissue RBP4 levels and metabolic disease, (1)(2)(3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16) there are a number of studies reporting evidence to the contrary, (29)(30)(31)(32) including ones that failed to establish associations between RBP4 and NAFLD. (33,34) Undoubtedly, some of this disagreement in the literature arises from differences in methodologies employed by different research groups, including methodologies needed for grouping and studying human subjects as well as laboratory techniques used to evaluate RBP4 levels and actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the reports from Yang et al (8) and Graham et al (9) a decade ago, there has been considerable research interest focused on understanding how RBP4 synthesized by adipocytes contributes to the development of metabolic disease, including liver disease. Although much of this literature reports associations between elevated serum/plasma and/or tissue RBP4 levels and metabolic disease, (1)(2)(3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16) there are a number of studies reporting evidence to the contrary, (29)(30)(31)(32) including ones that failed to establish associations between RBP4 and NAFLD. (33,34) Undoubtedly, some of this disagreement in the literature arises from differences in methodologies employed by different research groups, including methodologies needed for grouping and studying human subjects as well as laboratory techniques used to evaluate RBP4 levels and actions.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Retinol bound to RBP4 accounts for approximately 95% of the retinoid that is present in the fasting circulation. (7) Many investigators have reported findings that associate elevated RBP4 levels with the development of type 2 diabetes, (8)(9)(10)(11)(12) cardiovascular disease, (13)(14)(15)(16) as well as NAFLD. (1)(2)(3)(4)(5)(6) Kahn and colleagues proposed that the development of obesity leads to increased expression of RBP4 by adipocytes, influencing metabolic disease development.…”
mentioning
confidence: 99%
“…39 Moreover, in an animal model overexpressing RBP4, an earlyonset microglia activation followed by a progressive retinal degeneration mediated by an increased expression of pro-IL-18 was observed. 40 Therefore, RBP4 could be involved in the inflammatory process of DR and could be considered a biomarker of early stages of DR. Takebayashi et al 41 found elevated RBP4 levels in T2DM patients in comparison with nondiabetic subjects, and significant increased levels in patients with PDR versus no DR or nonproliferative DR. However, this relation was reduced after adjusting for urinary albumin excretion (UAE).…”
Section: Retinol-binding Proteinmentioning
confidence: 99%
“…In humans, serum RBP4 in obese and obese/diabetic patients was found Ïł1.5-3-fold higher when compared with lean controls (4 -7), and this increase was mirrored by elevated expression of RBP4 in adipose tissue (8). Mice deficient in RBP4 were more insulin sensitive than control littermates, whereas mice with transgenic expression of RBP4 were prone to high-fat diet (HFD)-induced insulin resistance (4), although not all studies could reproduce these phenotypes (9,10). Interestingly, the sole injection of Escherichia coli-derived recombinant RBP4 into mice led to impaired glucose tolerance (4,11).…”
mentioning
confidence: 99%